Enhancing Green Methanol Production via CO2 Hydrogenation: Process Intensification using Plug Flow Reactor and Vanden Bussche-Froment - Faiz Fairuz Zaki; Alifio Alifio; Muhammad Nur Irfan; Job Boas; Maulana Nizar Amrullah; Hanif Farrel Ardan (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
The transition to renewable energy in Indonesia requires strategic solutions for carbon capture and utilization (CCU). Methanol synthesis from captured CO2 and green hydrogen offers a promising pathway but is hindered by thermodynamic equilibrium limitations and high energy consumption in the purification section. This study aims to develop an intensified process design for green methanol production integrated with a Direct Methanol Fuel Cell (DMFC) using Aspen HYSYS V11, specifically focusing on optimizing yield via a Plug Flow Reactor (PFR) and the Vanden Bussche-Froment (VBF) kinetic equation. The simulation results demonstrated that the Plug Flow Reactor (PFR) configuration achieved a single-pass CO2 conversion of 21.4% at 250 °C and 50 bar, highlighting the baseline challenge of equilibrium limitations in a conventional setup. Furthermore, the implementation of Heat Integration via a Plug Flow Reactor (PFR) and the Vanden Bussche-Froment (VBF) kinetic equation significantly reduced the total external heating utility requirement by utilizing the sensible heat of the hot reactor effluent. This strategy effectively lowered the energy load on external heaters, replacing high-cost utility usage with efficient internal heat recovery. The integrated DMFC system showed a potential electrical efficiency of 42%. Conclusion: The proposed process intensification significantly enhances the techno-economic feasibility of green methanol plants in Indonesia, offering a sustainable solution for industrial decarbonization. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).